2019
DOI: 10.2147/ott.s158619
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of key pathways and hub genes in basal-like breast cancer using bioinformatics analysis</p>

Abstract: Background Basal-like breast cancer (BLBC) is the most aggressive subtype of breast cancer (BC) and links to poor outcomes. As the molecular mechanism of BLBC has not yet been completely discovered, identification of key pathways and hub genes of this disease is an important way for providing new insights into exploring the mechanisms of BLBC initiation and progression. Objective The aim of this study was to identify potential gene signatures of the development and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 36 publications
5
45
0
Order By: Relevance
“…Such pathways included signaling pathways like EIF2 and AHR, as well as pathways involved in mitosis and other molecular mechanisms of cancer. Both sets of genes also contained many gene ontology (GO) biological processes pertaining to the cell cycle, consistent with previous studies that found such enrichment in basal-like subtypes of breast cancer Yang, Gao and Luo, 2019). We further validated our results by testing for overlaps with known gene sets via GSEA analysis (Mootha et al, 2003;Subramanian et al, 2005).…”
Section: Numerical Examplessupporting
confidence: 88%
“…Such pathways included signaling pathways like EIF2 and AHR, as well as pathways involved in mitosis and other molecular mechanisms of cancer. Both sets of genes also contained many gene ontology (GO) biological processes pertaining to the cell cycle, consistent with previous studies that found such enrichment in basal-like subtypes of breast cancer Yang, Gao and Luo, 2019). We further validated our results by testing for overlaps with known gene sets via GSEA analysis (Mootha et al, 2003;Subramanian et al, 2005).…”
Section: Numerical Examplessupporting
confidence: 88%
“…4,5 Maternal embryonic leucine zipper kinase (MELK) is a member of the AMP protein kinase (AMPK) family of serine/threonine kinases, and MELK activates multiple cellular pathways that drive oncogenic growth. [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL). [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL).…”
Section: Introductionmentioning
confidence: 99%
“…The ATM-CHK2 pathway is activated when DSBs occur. MELK was proven to be associated with mitotic progression and DNA damage [8][9][10][11][12][13]. Kig et al confirmed that MELK was required for the repair of DNA damage (including dou-…”
mentioning
confidence: 99%
“…Of the genes associated with poor prognosis in patients with basal-like breast cancer in this study, CDC7 [13], KIF18A [9], and CKS2 [22] have previously been shown to be associated with breast cancer. STIL, also known as STIL centriolar assembly protein, encodes a cytoplasmic protein involved in the regulation of mitotic spindle checkpoints.…”
Section: Discussionmentioning
confidence: 92%